2018
DOI: 10.1177/1029864918762269
|View full text |Cite
|
Sign up to set email alerts
|

The role of positional knowledge and tonal approaches in cellists’ sight-reading

Abstract: Sight-reading is an important skill for amateur and professional musicians. Several factors seem to play a role in sight-reading skills, such as expertise level, ear training, mental speed and improvisation skills. If we are right in supposing that these factors cannot easily be generalized for all musicians, one of the reasons for this must surely lie in the fact that different musical instruments set different technical requirements for the player. The purpose of this study was to investigate which factors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
3
Order By: Relevance
“…LPV, basándose en su experiencia y en la experimentación durante las clases (Burwell, 2012;Daniel y Parkes, 2017;Gaunt, 2008;Lehmann y McArthur, 2002;Karlsson y Juslin, 2008;Simones, 2015). Casi todos los docentes adaptaron las estrategias a las dificultades de cada estudiante (Mishra, 2014(Mishra, , 2015 y a las características de sus instrumentos (Wolfz, Boshuizen y van Strien, 2018;Wurtz, Mueri y Wiesendanger, 2009). Aunque en casi todas las clases se empleó el análisis armónico, en ninguna se contextualizó con el periodo histórico o estilo para favorecer el desarrollo de expectativas (Wristen, 2005;Zhukov et al, 2016).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…LPV, basándose en su experiencia y en la experimentación durante las clases (Burwell, 2012;Daniel y Parkes, 2017;Gaunt, 2008;Lehmann y McArthur, 2002;Karlsson y Juslin, 2008;Simones, 2015). Casi todos los docentes adaptaron las estrategias a las dificultades de cada estudiante (Mishra, 2014(Mishra, , 2015 y a las características de sus instrumentos (Wolfz, Boshuizen y van Strien, 2018;Wurtz, Mueri y Wiesendanger, 2009). Aunque en casi todas las clases se empleó el análisis armónico, en ninguna se contextualizó con el periodo histórico o estilo para favorecer el desarrollo de expectativas (Wristen, 2005;Zhukov et al, 2016).…”
Section: Discusión Y Conclusionesunclassified
“…Findings also suggest that effective sight-reading strategies in the different musical instruments are necessary, but it is also essential to explore its applicability in real contexts and, above all, to favor a well-rounded instrumental music education. bles a otros instrumentos musicales (Wristen, 2005), varios investigadores consideran que es necesario entender las dificultades propias de cada uno durante la LPV para desarrollar enfoques pedagógicos adecuados (Wurtz, Mueri y Wiesendanger, 2009;Wolfs, Boshuizen y van Strien, 2018). Asimismo, aunque existen numerosos estudios sobre los procesos cognitivos involucrados en la LPV, pocas estrategias pedagógicas cuentan con suficiente respaldo empírico que sustenten su efectividad (Mishra, 2014;Wristen, 2005;Zhukov, 2016;Zhukov et al, 2016).…”
unclassified
“…Furthermore, participants with more years of musical experience tend to have better cross-modal integration abilities (i.e., improved audiovisual processing; Drai-Zerbib & Baccino, 2014 , 2018 ; Drai-Zerbib et al, 2012 ), which could facilitate the execution of sight-singing tasks. Therefore, it is not surprising that, as Wolfs et al (2020) observed, experience is a significant predictor of sight-reading performance among cellists, and according to Fournier (2020) , musical experience is correlated to aural skills performance when combining musical dictation and sight-singing scores. Consequently, it seems plausible that students who begin their postsecondary music education with more musical experience and a more extensive background in music reading should also be better at sight-singing.…”
Section: Musical Experiencementioning
confidence: 90%
“…Music sight-reading (MSR) is considered as important functional skill in Western musical domains that deals with several factors, including level of expertise, aural training, auditory imagery, mental and psychomotor, and improvisation skills (Wolfs, Henny and Strien 2018;Houghton 2018) among others. This skill is required in formal situations such institutional music examinations tests or orchestral entrance competitions involving therefore complex simultaneous tasks regarding visual, auditory and motor processing (Karacharova and Khmelnitskaya 2018;Fireman 2008).…”
Section: Introductionmentioning
confidence: 99%